High‐Performance Deep‐Blue OLEDs Harnessing Triplet–Triplet Annihilation Under Low Dopant Concentration. Issue 2 (27th September 2022) - Chen, Chia-Hsun; Li, Yung-Shin; Fang, Shao-Cheng; Lin, Bo-Yen; Li, Che-Yu; Liao, Yu-Chan; Chen, Deng-Gao; Chen, Yi-Ru; Kung, Yu-Cheng; Wu, Chi-Chi; Lin, Yulin; Hung, Wen-Yi; et al.
Abstract : Organic blue emitters capable of proceeding triplet–triplet annihilation (TTA) are of great importance for high‐efficiency blue organic light‐emitting diodes (OLEDs). Herein, two deep‐blue emitters PAPE and PAPF with two diphenylanthracene (DPA) moieties linked by fluorene and ether, respectively, together with a single DPA model emitter PAPES are synthesized and characterized. Theoretical calculations indicate that the TTA mechanism of these materials is energetically favorable, which is evidenced by platinum octaethylporphyrin‐sensitized TTA‐upconversion (UC) study. The OLED devices employing o ‐DiCbzBz host doped with a low concentration of (1%) PAPE and (3%) PAPF furnish superior maximum external quantum efficiency (EQEmax ) up to 7.3% and 7.2% and realize deep‐blue emissions with Commission International de L'Eclairge (CIE) coordinates of (0.15, 0.05) and (0.15, 0.04), respectively, that outperform the model device doped with (1%) PAPES with EQEmax 4.12%. The delayed emission lifetimes from TTA of PAPE ‐ and PAPF ‐doped devices observed by the time‐resolved electroluminescence (EL) analyses are rather short. Fast TTA is observed with magneto‐electroluminescence, supporting the possibility of intramolecular TTA operation in the devices. This work manifests the potential of multichromophoric strategy to design fluorescent emitters that is able to boost the efficiency of deep‐blue OLEDs even with a low doping concentration. Abstract : The molecule with two 9, 10‐diphenylanthracene groups bridged by an oxygen atom is investigated as fluorescent dopant. The deep‐blue device using a low‐concentration dopant furnishes a maximum external quantum efficiency up to 7.3%. Combining the studies of photoluminescence sensitization, transient electroluminescence, and magnetoelectroluminescence, the possibility of fast intramolecular triplet–triplet annihilation upconversion is proposed to account for the high efficiency.